Resilient Densification: Four studies from Johannesburg - Todes, Alison. Harrison, Phillip. Weakley, Dylan. (2015 University of the Witwatersrand, Gauteng City-Region Observatory, 2015)
Unlike most cities in the world, over the last 20 years Johannesburg has become more dense and more compact. This reflects the increased rates of rural-urban migration from the late 1980s as urbanisation controls collapsed, but also the relative success of Johannesburg’s economy and democratic-era policies to contain urban sprawl (such as the urban development boundary). The ending of apartheid regulations allowed a release in a pent-up demand for access to large cities with much of the movement directed to the three large metropolitan cities in Gauteng. Densification in the city has occurred in both planned and unplanned ways. In line with directions in planning internationally, post-apartheid planning has placed strong emphasis on urban densification and compaction. At the same time, however, market forces (both formal and informal) have driven densification in the city, in ways that are often unforeseen and sometimes contrary to city policies. In order to plan for further development and to respond effectively to the densification that has happened, and is occurring, research into the processes and effects of densification is clearly needed. In this work we use an “urban resilience lens” to investigate four forms of residential densification in Johannesburg, using four illustrative case-studies. We explore the effects that densification is having in the city, showing how diverse, complex and contingent it often is.
Keywords: Johannesburg || Densification || Urbanisation